Biosorption of Cr(vi) from aqueous solution using dormant spores of Aspergillus niger. Issue 67 (14th November 2018) - Ren, Binqiao; Zhang, Qiang; Zhang, Xiaochen; Zhao, Luyang; Li, Hanyang
Abstract : Spores of Aspergillus niger (denoted as A. niger ) were used as a novel biosorbent to remove hexavalent chromium from aqueous solution. Abstract : Spores of Aspergillus niger (denoted as A. niger ) were used as a novel biosorbent to remove hexavalent chromium from aqueous solution. The effects of biosorbent dosage, pH, contact time, temperature and initial concentration of Cr(vi ) on its adsorption removal were examined in batch mode. The Cr(vi ) uptake capacity increased with an increase in Cr(vi ) concentration until saturation, which was found to be about 97.1 mg g −1 at pH 2.0, temperature of 40 °C, adsorbent dose of 2.0 g L −1 and initial concentration of 300 mg L −1 . Scanning electron microscopy, energy dispersive X-ray spectroscopy, field-emission transmission electron microscopy (FETEM), XPS and Fourier-transform infrared spectroscopy were applied to study the microstructure, composition and chemical bonding states of the biomass adsorbent before and after spore adsorption. The mechanisms of chromate anion removal from aqueous solution by the spores of A. niger were proposed, which included adsorption of Cr(vi ) onto the spores followed by its reduction to Cr(iii ). The reduced Cr(iii ) was rebound to the biomass mainly through complexation mechanisms, redox reaction and electrostatic attraction. The removal of Cr(vi ) by spores of A. niger followed pseudo-second-order adsorption kinetics. Monolayer adsorption of Cr(vi ) was revealed by the better fitting of the Langmuir model isotherm rather than multilayer adsorption for the Freundlich model. The results indicated that A. niger spores can be used as a highly efficient biosorbent to remove Cr(vi ) from contaminated water.